Methodological Aspects Of Ensuring Innovative Activity And Balance Of Agricultural Cluster Development - Mirzaev Kulmamat Jonuzokovich; Azizkulov Bakhtiyor Khushvaktovich (Zien Journals, 2022)
The article describes ways to create high value-added products in line with the conditions of domestic and foreign markets through the formation of modern systems such as free economic zones, technoparks, clusters and methodological aspects of ensuring innovative activity and balance of agroservices cluster development.
Keywords: agroservices; cluster system; integration; innovation